Komunikasi Humas di Media Sosial Instagram: Studi pada Kantor Pertanahan Kabupaten Nias - Habib Ardi; Muhammad Alfikri (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
Government agencies are increasingly compelled to utilize social media as a means of more open and interactive public communication in the digital era. This study aims to analyze the effectiveness of public relations communication through Instagram at the Nias Regency Land Office using a qualitative phenomenological approach, in order to understand the experiences of public relations staff in managing digital communication. Informants were selected purposively, namely the public relations staff managing the Instagram account @kantahkabnias. Data were collected through interviews, observation, and documentation, with validity established through source triangulation, technique triangulation, and member checks. The findings reveal that Instagram serves as a medium for disseminating service information, documenting activities, and facilitating two-way communication through feed, stories, reels, comments, and direct message features. Communication effectiveness was assessed through several indicators, including interaction levels, accessibility of public information, admin responsiveness, and the capacity to build institutional transparency and image. The results demonstrate that Instagram is considerably effective in broadening information accessibility and fostering more responsive communication, although constraints remain, particularly limited human resources and the presentation of administrative content that has yet to fully engage the public